Persistent dry eye syndrome after and late functional outcomes of excimer laser correction for myopia (Ukrainian Journal of Ophthalmology, 2023)
Background: Laser In Situ Keratomileusis (LASIK) is the laser vision correction procedure of choice for refractive surgeons and accounts for 80% to 85% of the procedures. Dry eye syndrome (DES) is the most common complication of LASIK, with 20% of patients having this complication at 6 months after intervention. Chronic DES after LASIK can cause epithelial hyperplasia, which may be associated with myopic regression.Purpose: To assess the impact of DES after ELC for myopia on the late functional outcomes.Material and Methods: Sixty-five myopic patients (130 eyes) were divided into two groups, group 1 (a LASIK group) and group 2 (a FemtoLASIK group). The control group was composed of 40 individuals (80 eyes). An examination was performed before surgery and throughout the study and included manifest and cycloplegic refraction, corneal topography, anterior segment optical coherence tomography (AS-ОСТ), tear production, tear film stability and ocular surface staining. Follow-up duration was 12 months.Results: A myopic regression of 0.5 ± 0.1 D was observed in eyes with postoperative DES. At 6 months after ELC for myopia, study patients had a 10.7% incidence of myopic regression of 0.5 ± 0.1 D. The epithelial thickness in the central zone increased by 7.9 ± 0.25 µm, and in the peripheral zone, by 2.0 ± 0.3 µm; corneal irregularity measurement (CIM) increased to 3.01 ± 0.12 µm, and ocular surface staining score, from 0.22 ± 0.08 to 2.3 ± 0.08, over the follow-up period in patients with persistent DES. Patients without DES exhibited neither myopic regression nor ocular surface staining at 6 months, with their CIM values being in the range of 0.49–1.68 µm. An increase in the epithelial thickness in the central zone was by no more than 2.5±0.3 µm larger than that in the peripheral zone, and mean manifest refraction was +0.12 ± 0.1 D.Conclusion: First, we found that 10.7% of our study patients had signs of persistent DES and a myopic regression of 0.5 ± 0.1 D after ELC for myopia. Second, the post-ELC increase in central corneal epithelial thickness over the follow-up period was 37.5% smaller in patients without DES than in patients with DES. Third, corneal epithelial thickness values were 6.4% lower in patients with myopia than in individuals without refractive abnormalities. Fourth, corneal topography maps of patients with DES show irregular astigmatism, which causes a decreased quality of vision associated with changes in epithelial thickness and myopic regression after ELC for myopia. Finally, the presence of corneal epithelial fluorescein staining can be considered to be evidence of DES-induced damage to the epithelium after ELC for myopia.
Keywords: excimer laser correction; myopia; persistent dry eye syndrome; myopic regression